Macroeconomic Variable and It's Influence On Performance of Indonesian Islamic Banking - Pratama, Yoghi Citra (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
The purpose of this research is to analyze the macroeconomics variables that affect to the performance of Islamic banks in Indonesia. Methods used in this research is the Vector Auto regressive (VAR) / Vector Error correction model (VECM) to see the effect of the shock and the long-term effect on the performance of Islamic Banking. The results show that based on the analysis of IRF, the performance of Islamic banking having short-term shocks to fluctuations in macroeconomics variables but stable in the long term, and based on the variance decomposition, shocks of macro variables only gives little effect on the performance of Islamic banking.DOI:10.15408/aiq.v7i1.1359